Quantum Tunneling in Deformed Quantum Mechanics with Minimal Length - Xiaobo Guo; Bochen Lv; Jun Tao; Peng Wang (Advances in High Energy Physics)
In the deformed quantum mechanics with a minimal length, one WKB connection formula through a turning point is derived. We then use it to calculate tunneling rates through potential barriers under the WKB approximation. Finally, the minimal length effects on two examples of quantum tunneling in nuclear and atomic physics are discussed.